Non-perturbative field theoretical aspects of graphene and related systems - Olivares, J. A. Casimiro; Mizher, A. Julia [UNESP]; Raya, A. (Sociedad Mexicana de Fisica A C, 2022)
In this article, we review the dynamics of charge carriers in graphene and related 2D systems from a quantum field theoretical point of view. By allowing the electromagnetic fields to propagate throughout space and constraining fermions to move on a 2D manifold, the effective theory of such systems becomes a non-local version of quantum electrodynamics (QED) dubbed in literature pseudo or reduced QED. We review some aspects of the theory assuming the coupling arbitrary in strength. In particular, we focus on the chiral symmetry breaking scenarios and the analytical structure of the fermion propagator in vacuum and under the influence of external agents like a heat bath, in the presence of a Chern-Simons term, anisotropy and in curved space. We briefly discuss the major advances and some new results on this field.
Keywords: Constraining fermions; Electromagnetic fields; Quantum field theoretical